ln(6x-2)+1=ln(2x+7)

Simple and best practice solution for ln(6x-2)+1=ln(2x+7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for ln(6x-2)+1=ln(2x+7) equation:


Simplifying
ln(6x + -2) + 1 = ln(2x + 7)

Reorder the terms:
ln(-2 + 6x) + 1 = ln(2x + 7)
(-2 * ln + 6x * ln) + 1 = ln(2x + 7)
(-2ln + 6lnx) + 1 = ln(2x + 7)

Reorder the terms:
1 + -2ln + 6lnx = ln(2x + 7)

Reorder the terms:
1 + -2ln + 6lnx = ln(7 + 2x)
1 + -2ln + 6lnx = (7 * ln + 2x * ln)
1 + -2ln + 6lnx = (7ln + 2lnx)

Solving
1 + -2ln + 6lnx = 7ln + 2lnx

Solving for variable 'l'.

Move all terms containing l to the left, all other terms to the right.

Add '-7ln' to each side of the equation.
1 + -2ln + -7ln + 6lnx = 7ln + -7ln + 2lnx

Combine like terms: -2ln + -7ln = -9ln
1 + -9ln + 6lnx = 7ln + -7ln + 2lnx

Combine like terms: 7ln + -7ln = 0
1 + -9ln + 6lnx = 0 + 2lnx
1 + -9ln + 6lnx = 2lnx

Add '-2lnx' to each side of the equation.
1 + -9ln + 6lnx + -2lnx = 2lnx + -2lnx

Combine like terms: 6lnx + -2lnx = 4lnx
1 + -9ln + 4lnx = 2lnx + -2lnx

Combine like terms: 2lnx + -2lnx = 0
1 + -9ln + 4lnx = 0

Add '-1' to each side of the equation.
1 + -9ln + -1 + 4lnx = 0 + -1

Reorder the terms:
1 + -1 + -9ln + 4lnx = 0 + -1

Combine like terms: 1 + -1 = 0
0 + -9ln + 4lnx = 0 + -1
-9ln + 4lnx = 0 + -1

Combine like terms: 0 + -1 = -1
-9ln + 4lnx = -1

Reorder the terms:
1 + -9ln + 4lnx = -1 + 1

Combine like terms: -1 + 1 = 0
1 + -9ln + 4lnx = 0

The solution to this equation could not be determined.

See similar equations:

| 0.6*43= | | 6-24-8-6= | | 4/3x3.14x729000 | | a=b(1/c-1/d) | | x+x-2+x+12=73 | | -8d-5d+7d=73 | | -2(x^2-9x+9)= | | 17=-7x-7x-9 | | 5xsquared=30x | | y=16*(0.5) | | 9/10*6/1 | | 2(x-4)+5(x+7)=3(x-1)+8(x+2) | | -3(4)-8= | | 4(v+3)=-9v+38 | | 48x+12x^2=0 | | x+20+x-45+x-15+130+70=540 | | 0=x^2+12x+36-2 | | log[5]x+13-log[5]x-11=2 | | 0=x^2+12x+34 | | 20+4-2= | | 3-6x-6x=11+4-7x+x | | 16+40+6-2= | | 6m+9m+5m=-1 | | 8x-6(-1)=-18 | | 12x-8y=-8 | | 5/13=19/x | | a(x)=2x+40(2x+60) | | 20y=5x | | 2x+11=8x-2 | | 6(2g+1)= | | 6x-55+x^2=0 | | 6-4-18+3+12= |

Equations solver categories